(untitled) (Scientific Journal of Research Studies in Future Psychology, 2024)
The aim of this research was to establish a relation between intellectually disabled children’s motor growth and their social adaptability with caregivers’ quality of life. For this Purpose, a group of 100 educable intellectually disabled children has been selected as our sample group using availability sampling method and to measure social compatibility Asghar Dethatches questionnaire and to measure quality of life QOL questionnaire have been used. According to the results related to person correlation ، physical health ،social interaction،environmental health and mental health subscales are directly and meaningfully related to their social adaptability and physical health and social interaction subscales have meaningful and indirect correlation with their social incompatibility .From multivariable Regression analysis output to predict caregivers quality of life areas social compatibility according to intellectually disabled children’s motor growth ، it is clear that caregivers physical health ، social interaction and environmental health areas are being significantly affected by their intellectually disabled children’s motor growth. But mental health area is not affected by social compatibility and children’s motor growth.